The role of the enrichment activities in "Loughati Alkhalida" course in the development of Oral expression skills from the point of view of the female teachers - Alharbi, Fatema Obeid; Al-Tunisi, Nabilah Taher Ali (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to identify the role of enrichment activities in the course of my time Its strength is (172) teachers, one of the Arabic language teachers in the middle stage in Medina, and the study reached many results, the most important of which is: The role of enrichment activities in developing oral expression skills among middle school students from the point of view of the teachers came in a great extent, where they were In a row (vocal oral expression skills, intellectual oral expression skills, linguistic oral expression skills, survival oral expression skills), the study also reached many proposals that contribute to activating the role of enrichment activities to develop oral expression skills among middle school students, including: preparation The opportunity or time for female students to participate in planning and organizing activities, linking enrichment activities to the student’s environment and benefiting from them, and emphasizing that enrichment activities are supportive of creativity and excellence among students, and the study provided many recommendations, including: the educational administration’s interest in scientific and enrichment activities; And the need to include it within the curricula to link the theoretical aspect to the scientific aspect, and to support the teacher for the student’s positive interaction with the group’s opinion, and accept her point of view during listening.